PERUBAHAN EPISTEMOLOGI DUNIA: SERANGAN TERHADAP EPISTEMOLOGI KRISTEN YANG OBJEKTIF - Ronald Gunawan (The Way Jurnal Teologi dan Kependidikan, 2020)
Changes in World Epistemology: Attacks on Objective Christian Epistemology. In ancient times people knew the truth horizontally just good and bad. This methodology is not only used by Christian theists but for those who reject the existence of God as the foundation of truth. Until the 20th century, there was a new methodology used to achieve truth, which was very different from the old methodology, which is subjective truth or truth that depends on individuals who know. These changes are very large and spread everywhere from the start of philosophical thought, art, until now began to affect theology and faith today. This paper was written by combining the methods of literature study and deconstruction to the root of the problem to discuss the brief history of the characters who started this thought from Hegel to ignite Kierkegaard's thoughts and from there provide space for the New Age Movement to enter. Then the researcher will discuss how Christianity responds to this new methodology Biblically and finally gives implications in the form of how this methodology is used to provide answers related to questions that for hundreds or even thousands of years since the days of Ancient Greece and even before it has been questioned by humans.